Correlation of APACHE II and SOFA scores with length of stay in various surgical iIntensive care units - Milić, Morena; Goranović, Tatjana; Katančić, Jadranka (2009)
Abstract: The aim of this study was to evaluate the usefulness of using Acute Physiology and Chronic Health Evaluation (APACHE) II score and Sequential Organ Failure Assessment (SOFA) score as the predictors of length of stay (LOS) in various surgical intensive care units (ICUs) and to test the hypothesis that the significance of scoring for predicting LOS is greater in specialized surgical ICUs. We scored patients in a non-specialized general surgical ICU (n=328) and in a specialized cardiosurgical ICU (n=158) consecutively on admission (APACHE II-1st day; SOFA-1st day) and on third day of stay (APACHE II-3rd day; SOFA-3rd day) in a 4-month period. LOS and APACHE II /SOFA scores were significantly correlated both on admission and on third day of stay in the general surgical ICU (APACHE II- 1st day r=0.289; SOFA-1st day r=0.306; APACHE II-3rd day r=0.728; SOFA-3rd day r=0.725). LOS and APACHE II on admission were not significantly correlated in the cardiosurgical ICU (APACHE II-1st day r=0.092), while SOFA on admission and APACHE II and SOFA on third day were significantly correlated (SOFA-1st day r=0.258; APACHE II-3rd day r=0.716; SOFA-3rd day r=0.719). Usefulness of scoring for predicting LOS in ICU varied between different surgical ICUs. Contrary to our hypothesis, scoring had greater value for predicting LOS in the non-specialized general surgical ICU. APACHE II score on admission had no value for predicting LOS in the cardiosurgical ICU
Bibliografija: 7 jed
Sažetak
Keywords: Acute Physiology and Chronic Health Evaluation -- Sequential Organ Failure Assessment -- Kirurška jedinica za intenzivno liječenje